High‐Density Lipoprotein Cholesterol Concentration and Acute Kidney Injury After Cardiac Surgery - Loren E. Smith; Derek K. Smith; Jeffrey D. Blume; MacRae F. Linton; Frederic T. Billings (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundAcute kidney injury (AKI) after cardiac surgery is associated with increased short‐ and long‐term mortality. Inflammation, oxidative stress, and endothelial dysfunction and damage play important roles in the development of AKI. High‐density lipoproteins (HDLs) have anti‐inflammatory and antioxidant properties and improve endothelial function and repair. Statins enhance HDL's anti‐inflammatory and antioxidant capacities. We hypothesized that a higher preoperative HDL cholesterol concentration is associated with decreased AKI after cardiac surgery and that perioperative statin exposure potentiates this association. Methods and ResultsWe tested our hypothesis in 391 subjects from a randomized clinical trial of perioperative atorvastatin to reduce AKI after cardiac surgery. A 2‐component latent variable mixture model was used to assess the association between preoperative HDL cholesterol concentration and postoperative change in serum creatinine, adjusted for known AKI risk factors and suspected confounders. Interaction terms were used to examine the effects of preoperative statin use, preoperative statin dose, and perioperative atorvastatin treatment on the association between preoperative HDL and AKI. A higher preoperative HDL cholesterol concentration was independently associated with a decreased postoperative serum creatinine change (P=0.02). The association between a high HDL concentration and an attenuated increase in serum creatinine was strongest in long‐term statin‐using patients (P=0.008) and was further enhanced with perioperative atorvastatin treatment (P=0.004) and increasing long‐term statin dose (P=0.003). ConclusionsA higher preoperative HDL cholesterol concentration was associated with decreased AKI after cardiac surgery. Preoperative and perioperative statin treatment enhanced this association, demonstrating that pharmacological potentiation is possible during the perioperative period. Clinical Trial RegistrationURL: http://www.clinicaltrials.gov. Unique Identifier: NCT00791648.